Immunohistochemical Detection of Cancer-Testis Antigen PRAME. (December 2021) - Lezcano, Cecilia; Müller, Annette M.; Frosina, Denise; Hernandez, Enmily; Geronimo, Jerica A.; Busam, Klaus J.; Jungbluth, Achim A.
Cancer-testis (CT) antigens were identified by their ability to elicit T- or B-cell immune responses in the autologous host. They are typically expressed in a wide variety of neoplasms and in normal adult tissues are restricted to testicular germ cells. PReferentially expressed Antigen of Melanoma (PRAME) is a member of the family of nonclassical CT antigens being expressed in a few other normal tissues besides testis. Interestingly, knowledge about the protein expression of many CT antigens is still incomplete due to the limited availability of reagents for their immunohistochemical detection. Here, we tested several commercially available serological reagents and identified a monoclonal antibody suitable for the immunohistochemical detection of PRAME in formalin-fixed paraffin-embedded specimens. We also tested a wide array of normal and neoplastic tissues. PRAME protein expression in normal tissues is congruent with original molecular data being present in the testis, and at low levels in the endometrium, adrenal cortex, and adult as well as fetal ovary. In tumors, there is diffuse PRAME immunoreactivity in most metastatic melanomas, myxoid liposarcomas, and synovial sarcomas. Other neoplasms such as seminomas and carcinomas of various origins including endometrial, serous ovarian, mammary ductal, lung, and renal showed an intermediate proportion of cases and variable extent of tumor cells positive for PRAME protein expression. As seen with other CT antigens, hepatocellular and colorectal carcinoma, Leydig cell tumors, mesothelioma, and leiomyosarcoma are poor expressers of PRAME.